The condensed handbook of measurement and control - Battikha, N. E. (Research Triangle Park, NC ISA, 2018)
"Selecting and implementing measurement and control devices for process automation applications is made easier with this best-selling reference. This clear and concise fourth edition provides quick access to ISA symbology, instrument and control valve selection criteria, and conversion guidelines, with new sections on maintenance, calibration, decision-making skills, and consulting. Whether you are an experienced engineer, technician, salesperson, or project manager, or new to the field, you will better understand how to assess, compare, and select the various methods of measurement and control with this valuable and economical handbook in your library." --
Introduction -- Identification and symbols -- Analyzers -- Flow measurement -- Level measurement -- Pressure measurement -- Temperature measurement -- Control loops -- Programmable electronic systems -- Alarm and trip systems -- Control centers -- Enclosures -- Control valves -- Engineering design and documentation -- Installation -- Check-out, commissioning, and start-up -- Maintenance -- Calibration -- Project implementation and management -- Decision-making tools -- Road to consulting -- Appendix A. Unit conversion tables -- Appendix B. Corrosion resistance/Rating guide -- Appendix C. The engineering contractor -- Appendix D. Packaged equipment -- Appendix E. Engineering scope of work -- Appendix F. Development of corporate standards and guidelines -- Appendix G. Typical job titles and descriptions -- Appendix H. Sample audit protocol -- Appendix I. Sample audit report -- Appendix J. Sample control panel specification.
Includes bibliographical references and index.
Keywords: Process control -- Instruments; Measuring instruments